The Economy of British America, 1607-1789 - McCusker, John J. (Book collections on Project MUSE., 1985)
By the American Revolution, the farmers and city-dwellers of British America had achieved, individually and collectively, considerable prosperity. The nature and extent of that success are still unfolding. In this first comprehensive assessment of where research on prerevolutionary economy stands, what it seeks to achieve, and how it might best proceed, the authors discuss those areas in which traditional work remains to be done and address new possibilities for a 'new economic history.'